Strategies For Management Of Teachers ‘Resource Centres To Support Teachers ‘Professional Development-Lessons From Dodoma Region, Tanzania - Tibyehabwa, Revelian; Chiwanga, Rahel; Olofea, Huruma (Journal of Danubian Studies and Research, 2023)
Objective; this qualitative study is about investigating experiential management strategies used by Local Government Authorities (LGAs) in improving Teacher Resource Centres (TRC) to support teachers’ professional development (TPD). Prior or originality of study; the study was carried out because management of TRCs in Tanzania was under Ministry of Science and Technology before commencement of LGAs in 1982 which led to the decentralization of public services to carter for service delivery. Approach; purposive sampling was employed to get participants to include in the study. Data were collected by using documentary review, observation and semi-structured interview methods, and analysed thematically. Results; the study found that DPEOs and TRC Coordinators use tutors from schools, rent TRCs buildings for public activities, share other institutions resources, use school competitions to acquire teaching materials, secure funds from banks, and Children in Crossfire and Education Quality Improvement Programmes as education programmes improve operation of TRCs. Implication; TRCs are optional places for in-service training to support TPD, management of TRCs lack formal budget from the LGAs’ education management structure, and challenges limiting TRCs activities are human, material and financial resources. Value; the study is useful particularly in policymaking, enhancement of TPD and improvement of quality of TRCs.